British foreign policy : the process of readjustment, 1945-1961 - Northedge, F. S. (New York, Praeger, 1962)
An account of Britain's role in the world from the Second World War to the decision to apply for membership of the European Economic Community in 1961. These sixteen years form a distinct epoch, marking Britain's transition from worldwide Imperial status to that of an essentially European country. This book examines the accompanying process of readjustment and considers how well the British people and their governments have faced it.
Includes bibliographical references (pages 332-336).
Keywords: Since 1945; World politics -- 1945-1989.; Diplomatic relations